Prescription pattern of antibiotics in various clinical departments of a tertiary care health institution: a retrospective observational study - Ramesh; Vadhwa, Meenakshi; Ridhima (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Antimicrobial resistance has been considered as one of the greatest challenges to the general public health today. The Antibiotic Stewardship Program has emphasized on prevention of drug resistant bacterial infection, targeted therapy against susceptible or resistant microorganism and to curtail unnecessary and irrational use of antibiotics. Present study aimed to evaluate the pattern of antibiotic prescription amongst the hospitalized patients of IGMC Shimla in Himachal Pradesh. Methods: It was a retrospective observational study. Data was collected from hospital records of admitted patients in medicine and Surgical wards. Patient data like demographic profile, average hospital stay and number of antibiotics prescribed were extracted from their hospital records. Also, the data about oral/parenteral, generic/branded empirical/definitive and therapeutic/prophylaxis prescription in each patient were collected. Results: In medicine ward, the number of generic prescriptions 78 (71.5%) were more as compared to branded 31 (28.5%) and majority were given the parenteral 61 (55.9%) than the oral 48 (44.1%) dosage form. In surgery ward, the branded prescriptions 61 (91%) out-numbered the generic prescription 6 (9%). The route of administration was mostly oral; 56 (83.5%), while only few had parenteral prescription; 11 (16.5%) in this ward. Conclusions: It was found that majority of patients in medicine ward received generic named antibiotics for definitive management, while in surgical ward branded named antibiotics were prescribed for surgical prophylaxis. The cephalosporin was the most commonly prescribed antibiotic group. Majority of antibiotics belonged to “watch” category as far as WHO’s AWaRe classification is concerned.